Tafsir Syafahi Ahmad Bahaudin Nur Salim : Studi Analisis Karakteristik Kelisanan Dan Penafsiran - Ahmad Maymun; Muhammad Ulinnuha; Samsul Ariyadi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This study examines KH. Ahmad Bahaudin Nur Salim From the characteristics of his orality, Ahmad Bahaudin Nur Salim uses the orality theory of Walter J. Ong and analyzes the ideology of Ahamad Bahaudin Nur Salim's interpretation from the point of view of theology and fiqh. This study uses a type of library research. The presentation of the data in this paper is in the form of descriptive-analysis, decoding the data of Syafahi KH. Ahmad Bahauddin Nursalim, namely the writer, will describe the discussion as it is from recorded data in the form of video and audio on the Official YouTube channel LP3IA, Santri Gayeng, and Tafsir NU and then filtered according to the research that the author will examine, namely the interpretation of KH. Ahmad Bahauddin Nursalim regarding the verses that the author has chosen according to the theme discussed. The author's findings show that from the 10 verses discussed by the author, it can be taken as a common thread that in general the characteristics of Gus Baha's speech fulfill the 5 characteristics of the theory of speech offered by Walter J Ong. In terms of the interpretation, the author can say that Ahmad Bahaudin Nur Salim's syafahi interpretation follows Sunni Ash'arî theology, in terms of fiqh he follows the  Syafi'i madhhab.